PENGARUH EFEKTIFITAS SISTEM PERPAJAKAN DAN PELAYANAN FISKUS TERHADAP KEMAUAN UNTUK MEMBAYAR PAJAK DENGAN KESADARAN MEMBAYAR PAJAK SEBAGAI VARIABEL INTERVENING - Popi Fauziati; Arfin Syahri (Akuntabilitas, 2015)
This research aims to know the influential factors of willing to pay tax with theirawareness of paying it as intervening variable particularly in Payakumbuh City. This researchused variable independent; those are perception about taxation efficacy system, tax officersservice. Intervening variable was the awareness of paying the tax. While, dependent variablewas willing to pay the tax. This research used primary data by using questionnaire.Respondents were all individual tax payer who became self employeed in Payakumbuh city.Method of taking sample in this research used random sampling. The data analysis usingregression analysis. The results of this data processing showed that: (1) perception of thetaxation efficacy system has significant influence toward the awareness of paying the tax. (2)tax financial service have significant influence toward the awareness of paying the tax (3) theawareness of paying the tax have significant influence toward tax payers’ willing to pay taxDOI: 10.15408/akt.v8i1.2761